Efforts to Fulfill the Economic Rights of Women and Children After Talak Divorce in Gorontalo Religious Court - Siti Mutmaina Suci Lasri Isra; Nur Mohamad Kasim; Weny Almoravid Dungga (Jurnal Cakrawala Hukum, 2026)
Divorce cases, particularly cerai talak (husband-initiated divorce), have increased significantly at the Gorontalo Religious Court over the past three years, raising serious concerns regarding the fulfillment of the economic rights of women and children following marital dissolution. This article analyzes the judicial efforts undertaken to protect and fulfill the economic rights of women and children in cerai talak cases at the Gorontalo Religious Court. The purpose of this article is to examine both preventive and repressive measures employed by judges in ensuring that rights such as mutah, iddah maintenance, child support, and division of marital assets are adequately addressed within court rulings. A normative-juridical method was employed through a case approach and statute approach. The findings prove that while judges have made considerable efforts through active fact-finding, mediation, and ex officio authority, the effectiveness of these rulings remains substantially hindered by low legal literacy among women, weak post-judgment execution mechanisms, and limited access to legal aid. It is therefore recommended that institutional strengthening, inter-agency synergy, and the consistent optimization of judges' ex officio authority are essential to ensuring that legal protection for women and children extends beyond formal court decisions into substantive justice